Astaxanthin-folic acid combined treatment potentiates neuronal regeneration and functional recovery after brachial plexus avulsion and reimplantation - Huang, Chao; Li, Zehui; Qu, Wenrui; Guo, Wenlai (Frontiers in Neuroscience, 2022)
Brachial plexus avulsion (BPA), which commonly occurs in neonatal birth injuries and car accidents, severely disrupts spinal cord segments and nerve roots. Avulsion is usually located in the transitional zone at the junction of spinal nerve roots and starting point of the spinal cord, which places heavy disability burdens on patients due to sensory and motor function loss in the innervated areas. Primary mechanical injuries and secondary pathogenesis, such as inflammatory infiltration and oxidative stress, lead to inefficient management and poor prognosis. Astaxanthin (AST) has a strong ability to bleach singlet oxygen and capture free radicals, quench singlet oxygen and trap free radicals, and folic acid (FC) can effectively inhibit the inflammatory response. This study aimed to investigate the therapeutic effects of AST and FC on BPA. The 24 h after BPA was considered the acute phase of the injury, and the combination of AST and FC had the best therapeutic effect due to the synergistic effect of AST’s antioxidant and FC’s anti-inflammatory properties. At 6 weeks after BPA, AST-FC promoted the recovery of biceps motor functions, increased myofiber diameter, enlarged the amplitude of musculocutaneous nerve-biceps compound action potential, and improved Terzis grooming test (TGT) scores. Meanwhile, more functional ventral horn motor neurons in the spinal cord were maintained. In conclusion, AST-FC combined therapy has a potential role in the clinical management of BPA since it can effectively alleviate oxidative stress and the inflammatory response in the acute phase of BPA, increase the survival rate of neurons, and promote neuronal regeneration and recovery of motor functions in the late stage of BPA.